Evaluation of film-forming potential of a natural gum - Panda, D S; Choudhury, N S K; Yedukondalu, M; Si, S; Gupta, R (Asian Journal of Pharmaceutics (AJP), 2014)
Films were prepared using 5 parts of 10% w/w of mucilage of gum of Moringa oleifera with different proportions of plasticizers: polyethylene glycol (PEG 400) (0.1, 0.15, 0.2, and 0.3), glycerin (0.15), and propylene glycol (0.2). The films were casted on glass plates and dried under controlled evaporation. Films prepared with 0.15, 0.2 part of PEG 400; 0.15 part of glycerin and propylene glycol showed satisfactory drying after 24 h. They were evaluated for following parameters water uptake, tensile strength, folding endurance, and water vapor transmission rate. The results obtained are comparable with films made from other polymers, and the gum can be used for preparing polymeric drug delivery systems and as film coating agent.